Physicochemical Treatment of Sugar Industry Wastewater: Coagulation Processes. Issue 4 (April 2014) - Sahu, Om Prakash; Chaudhari, Parmesh Kumar
<x xml:space="preserve">Abstract</x> A case study from India identifies optimal dosages and pH